2001
DOI: 10.2737/pnw-gtr-518
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the social acceptability of natural resource decisionmaking processes by using a knowledge base modeling approach.

Abstract: Kakoyannis, Christina; Shindler, Bruce; Stankey, George 2001. Understanding the social acceptability of natural resource decisionmaking processes by using a knowledge base modeling approach. Gen. Tech. Rep. PNW-GTR-518. Portland, OR: U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station. 40 p. Natural resource managers are being confronted with increasing conflict and litigation with those who find their management plans unacceptable. Compatible and sustainable management decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 68 publications
0
16
0
1
Order By: Relevance
“…Although a number of publications have dealt with social acceptability in subject areas including health or environmental risk [24][25][26] or forestry management [27][28][29], the social acceptability of protected areas remains a poorly explored area of research.…”
Section: What Is Social Acceptability?mentioning
confidence: 99%
“…Although a number of publications have dealt with social acceptability in subject areas including health or environmental risk [24][25][26] or forestry management [27][28][29], the social acceptability of protected areas remains a poorly explored area of research.…”
Section: What Is Social Acceptability?mentioning
confidence: 99%
“…Taylor and Daniel (1984) found no significant difference for visual and recreational acceptability of prescribed fire between respondents that were informed and not informed. However, they also found that information increased public tolerance and understanding of fire; a finding supported by Kakoyannis et al (2001). Ford et al (2009b) found that information about the consequences of forest management activities changed the relative acceptability of alternative harvesting treatments.…”
Section: Education and Informationmentioning
confidence: 85%
“…Kakoyannis et al (2001) suggest that "the main role of science in natural resource management is to provide information about different alternatives that can assist managers in making decisions to achieve societal goals". This suggests that resource managers should provide a range of options, presenting information about the relative advantages and disadvantages, with the goal of finding a position that has wider acceptance (although it is unlikely that all opposing viewpoints can be accommodated).…”
Section: Information and The Management Of Risk Perceptionsmentioning
confidence: 99%
See 2 more Smart Citations